The Performance Effects of Individual and Group Incentives: A Case Study - Takao Kato; Antti Kauhanen; Essi Kujansuu (The Research Institute of the Finnish Economy (ETLA), 2013)
We study a warehouse that changes its incentive plan from a group plan to an individual plan. We focus on the impact that the change had on productivity, allocation of time to different tasks, and helping across departments. Utilizing time series methods we find that average productivity increased about 15 % but that individuals reacted heterogeneously to the change. The change also affected the organization of helping across departments and the allocation of time to various tasks. In addition to the econometrics analysis we provide a description of the process of changing the incentive plan and discuss the cost effectiveness of the change of the plan.
Keywords: 330